Battle in the Mind Fields - Goldsmith, John A. (University of Chicago Press, 2019)
This work is a study of linguistics and its neighbouring disciplines - psychology, logic, and philosophy - from ca. 1840 up until 1940 and the outbreak of World War II, that aims to give the reader an entirely new sense of where these disciplines came from and what their impact has been on the way we think about language and thought today.